2014
DOI: 10.1016/j.immuni.2014.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Recognition Receptor Signaling in Human Dendritic Cells is Enhanced by ICOS Ligand and Modulated by the Crohn’s Disease ICOSLG Risk Allele

Abstract: Summary Inflammatory bowel disease (IBD) is characterized by dysregulated intestinal immune homeostasis and cytokine secretion. Multiple loci are associated with IBD, but a functional explanation is missing for most. Here we found that pattern-recognition receptor (PRR)-induced cytokine secretion was diminished in human monocyte-derived dendritic cells (MDDC) from rs7282490 ICOSLG GG risk-carriers. Homotypic interactions between the co-stimulatory molecule ICOS and the ICOS ligand on MDDCs amplified nucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 45 publications
3
77
4
Order By: Relevance
“…22 In the HapMap database, ICOSLG rs7282490 shows strong linkage disequilibrium with the ICOSLG rs2838519 genetic polymorphism, which is associated with both PBC and CD susceptibility in the present study. These reports indicate that loss of function in ICOSLG rs7282490 might be associated with a shared clinical feature, granuloma formation, in both diseases.…”
Section: Discussionsupporting
confidence: 54%
“…22 In the HapMap database, ICOSLG rs7282490 shows strong linkage disequilibrium with the ICOSLG rs2838519 genetic polymorphism, which is associated with both PBC and CD susceptibility in the present study. These reports indicate that loss of function in ICOSLG rs7282490 might be associated with a shared clinical feature, granuloma formation, in both diseases.…”
Section: Discussionsupporting
confidence: 54%
“…Intestinal lamina propria cell isolation. Intestinal lamina propria cells were isolated from colonic resection specimens from uninvolved intestine in 7 non-IBD patients undergoing surgery for diverticular disease or colon cancer (9). mRNA expression analysis.…”
Section: Author Contributionsmentioning
confidence: 99%
“…In intestinal tissues, multiple other PRRs are activated, the outcomes of which might in turn be modulated by additional IBD risk loci. Polymorphisms resulting in both decreased (e.g., NOD2, IL18RAP, ICOSL, ATG16L1, CARD9) and increased (e.g., MAP3K8, TNFSF15, IRF5) PRR-mediated signaling and downstream outcomes can be associated with intestinal inflammation (2)(3)(4)(5)(6)(7)(8)(9)(10)(11), thereby highlighting the critical role of balance in regulation of PRR-initiated outcomes in intestinal tissues. Despite the success in identification of IBD-associated loci (12), altered functions for most of the IBD loci are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…PKCs consist of conventional PKCs (eg, PKCα and β) and atypical PKCs (eg, PKCζ), and we previously found that both PKC types contribute to NOD2-initiated cytokine secretion. 31 Upon successful knockdown of PKCα, β and ζ (figure 4F), we found that each kinase was required for TPL2 phosphorylation on Thr290 (figure 4G). Knockdown of MAPKs, which have not been reported to affect upstream TPL2 signalling, did not affect TPL2 phosphorylation (data not shown).…”
Section: Prr Stimulation Regulates Tpl2 Expressionmentioning
confidence: 97%